Some properties of the sequence space BV?(M,p,q,s) - Isik, Mahmut; Altin, Yavuz; Et, Mikail (Springeropen, 2013)
In this paper we define the sequence space BV theta (M, p, q, s) on a seminormed complex linear space by using an Orlicz function. We give various properties and some inclusion relations on this space.
Keywords: Orlicz function; sequence spaces; seminorm